MiR-22 suppresses epithelial–mesenchymal transition in bladder cancer by inhibiting Snail and MAPK1/Slug/vimentin feedback loop - Xu, Mingjie (Cell Death Dis, 2018)
MicroRNAs (miRNAs) have been validated to play prominent roles in the occurrence and development of bladder cancer (BCa). MiR-22 was previously reported to act as a tumor suppressor or oncomiRNA in various types of cancer. However, its accurate expression, function, and mechanism in BCa remain unclear. Here, we find that miR-22 is frequently downregulated in BCa tissues compared with adjacent non-cancerous tissues. Overexpression of miR-22 significantly inhibits proliferation, migration, and invasion of BCa cells both in vitro and in vivo. Importantly, miR-22 is found to suppress cell proliferation/apoptosis by directly targeting MAPK1 (mitogen-activated protein kinase 1, ERK2) and inhibit cell motility by targeting both MAPK1 and Snail. Further statistical analysis shows that low-expression of MAPK1 or Snail is an independent prognostic factor for a better overall survival in patients with BCa (n = 401). Importantly, we describe an important regenerative feedback loop among vimentin, Slug and MAPK1 in BCa cells. MAPK1-induced Slug expression upregulates vimentin. Vimentin in turn activates MAPK1. By inhibiting Snail and MAPK1/Slug/vimentin feedback loop, miR-22 suppresses epithelial–mesenchymal transition (EMT) of BCa cells in vitro as well as in vivo. Taken together, this study reveals that miR-22 is critical to the proliferation, apoptosis and EMT progression in BCa cells. Targeting the pathway described here may be a novel approach for inhibiting proliferation and metastasis of BCa.